Real world study on combining local interventions with systemic therapy in unresectable hepatocellular carcinoma - Zhaosong Xue; Ming Yao; Kang Chen; Taiyun Huang; Jianjun Li; Jian Chen; Fei Huang; Yubin Huang; Xiaoyong Cai; Yihe Yan (Scientific Reports)
Abstract  Combining local interventions with tyrosine kinase inhibitors (TKIs) plus anti-PD-1 antibodies in a triple therapy has demonstrated remarkable anti-tumor efficacy and facilitated conversion resection in patients with initially unresectable hepatocellular carcinoma (HCC). However, the long-term survival outcomes remain largely unexplored. This study focused on a cohort of consecutive patients who underwent triple therapy for initially unresectable HCC at the authors’ hospital between January 2020 and December 2022. Specifically, patients who exhibited a positive response to triple therapy and fulfilled the criteria for hepatectomy were selected for liver resection. Additionally, investigation assessed association between clinical factors and successful achievement of conversion resection, as well as postoperative recurrence. The study cohort comprised 79 patients, among whom 20 individuals (25.3%) underwent R0 resection subsequent to the initiation of triple therapy. Notably, patients without extrahepatic disease and those who exhibited a radiographic response to triple therapy were more likely to be eligible for curative resection. Importantly, hepatectomy independently associated with a favorable overall survival (HR, 0.388; 95% CI, 0.177–0.847; P = 0.017). Other independent risk factors related to overall survival contained extrahepatic metastasis (HR, 2.152; 95% CI, 1.076–4.302; P = 0.030), tumor number ≥ 4 (HR, 2.058; 95% CI, 1.001–4.234; P = 0.049) and radiological remission (HR, 0.233; 95% CI, 0.071–0.768; P = 0.017). For the 20 patients who underwent surgery, 12-month recurrence-free survival and overall survival rates were respectively 43.3% and 66.6%. The triple therapy demonstrated favorable prognostic outcomes and manageable safety profiles in patients with initially unresectable HCC.